Gelatin based films capable of modifying its color against environmental pH changes - Musso, Yanina Soledad (2016)
The aim of this work was to develop biodegradable protein-based films capable of sense pH changes. These protein films were prepared by casting from aqueous solutions of bovine gelatin, glycerol and three acid-base indicators: methyl orange (MO), neutral red (NR) and bromocresol green (BCG), at pH 2, 6 and 11. All resulting protein films were homogeneous, thin and had different colors depending on pH and the indicator used. The response of these materials was evaluated simulating their contact with liquid and semisolid media, and with a container headspace at acid and alkaline pH. In all tests, developed protein films could modify their color after being in contact with media of different pH. The physicochemical properties of films were also affected differently by the presence of each acid-base indicator. While the addition of BCG did not significantly modify the properties of control gelatin films, except its color; the incorporation of MO and NR into film-forming solutions significantly improved mechanical properties and decreased the water solubility and moisture content of the resulting protein films without affecting their water vapor permeability.